언어 입력의 일관성에 관한 코퍼스 기반 연구 - 강준수; 이영희 (영어학연구, 2023)
With a view to the consistency of language input and learning experience, this study aims to investigate the lexical coverage levels and lexical attributes in middle-school English textbooks developed under the current 2015 revised national curriculum. To that end, twelve different types of third-grader middle-school English textbooks were compiled as benchmark and study corpora and compared in terms of lexical coverage, lexical diversity, mean word length, and mean sentence length. The results found that three out of twelve textbooks did not satisfy the lexical coverage level of the benchmark corpus, while eight textbooks did not reach the lexical diversity level. Additionally, three out of twelve exceeded the mean word length. Finally, six textbooks fell below the mean sentence length of the benchmark corpus. These results underscore the importance of considering the consistency of language input and homogeneity in learner experience when developing middle-school English textbooks. The results suggest that the current national curriculum has room for improvement; it is recommended that the 2022 national curriculum be more closely aligned with these vital elements for a better student educational experience. KCI Citation Count: 1